Analysis of Student's Creative Thinking Ability Based On Gender Perspective On Reaction Rate Topic - Ella Izzatin Nada; Wiwik Kartika Sari* (Universitas Syiah Kuala, 2022)
Everyone has different creative potential. These differences can be influenced by experience, thinking patterns, ways of determining points of view, and other factors, including gender. This study aims to describe the profile of student's creative thinking skills from a gender perspective. The subjects were 450 high school students at Semarang City. The method used in this research is descriptive based on a comparative quantitative approach by using a test instrument. The test used in this study is a description test which consists of 10 questions arranged using Taxonomy Marzano. The results showed that the creative thinking skills between male and female students generally did not significantly differ. The differences in the characteristics of creative thinking skills can be seen in the fluency, flexibility, and elaboration indicators, while on the originality indicator, there is no significant difference. Differences in characteristics in this study are caused by differences in reasoning patterns between male and female students in solving given chemical problems. Male students tend to express many ideas and varied reasoning answers, while female students detail the solutions they put forward.